Studying the Significance of Aesthetic Education on Choral Classes at Junior High School in Shenyang, for Writing an Aesthetic Education on Choral Guidebook for Teachers - Jiali, Yu; Roongruang, Panya (Journal of Roi Kaensarn Academi, 2024)
The purpose of this study are (1) To study the significance of Aesthetic Education on choral classes in junior high school. (2) To create a" Choral Aesthetic Education Teaching Guidebook "for Teachers. (3) To use the guidebook for experiment teaching. (4) To evaluate the result of teaching by using the guidebook. The research method is a mixture of qualitative and quantitative methods. The qualitative research was conducted by interviewing 3 experts, making a guidebook for junior high school chorus teaching. Quantitative research is the use of teaching guidebook for experimental teaching. The population consisted of 28 schools participating in Shenyang Junior High School chorus Art Exhibition. Among them, 5 schools were randomly sampled, with 40 students in each school, totaling 200 students. The research results are as follows: (1) Study a large number books in chorus and aesthetic education, learn Kodaly music teaching method online, learn chorus methods and skills from three chorus experts, and understand the current development of chorus in Shenyang junior high school through key informants. (2) The Choral Aesthetic Education Teaching Guidebook consists of Basic construction of chorus, basic vocal skills, breathing, intonation, rhythm, solfeggio, song analysis and background explanation, etc. (3) The researcher designed 16 teaching plans and carried out experimental teaching according to the teaching guidebook. (4) The teaching effect of the choral teaching guidebook is obvious, This guidebook is used in the chorus teaching of junior high school. The students' learning outcomes are at a good level; This guide is suitable for high level teaching.